Inhibition of Escherichia coli by thioglycerol. - Jensen, K K (1981)
Thioglycerol inhibits the growth of various Escherichia coli strains and other microorganisms, both gram positive and gram negative. The susceptibility of organisms varies. The bactericidal action of this substance is not continuous and stops after an initial burst. At subbactericidal concentrations synthesis of ribonucleic acid is the most strongly affected. This is not due to interference with nucleoside biosynthesis or to direct inhibition of ribonucleic acid polymerase by thioglycerol.